Answer: The vertex of the given function is (2, -3).
Step-by-step explanation: We are given to find the vertex of the following function :
![y=x^2-4x+1~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vgrmfwcx5czt75i7j6n2hqc4sr8448d18v.png)
We know that
the vertex form of a function with vertex at the point (h, k) is given by
![y=a(x-h)^2+k.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/38h8hb85t2patkalw74fny15t9xp3kks0n.png)
From equation (i), we have
![y=x^2-4x+1\\\\\Rightarrow y=(x^2-4x+4)+1-4\\\\\Rightarrow y=(x-2)^2-3\\\\\Rightarrow y=(x-2)^2+(-3).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/m5kwbfxp2a4b80dkbgiuqjaesc9e486hh6.png)
Comparing the above equation with the vertex form, we get that the vertex of the given function is (2, -3).
Thus, the vertex of the given function is (2, -3).